Postnatal bladder dysfunction - V., Swathi H.; Samant, Padmaja Y. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Voiding difficulty and urinary retention is a common phenomenon in immediate postpartum period. Absolute or relative failure to empty the bladder resulting from decreased bladder contractility (magnitude or duration) or increased bladder outlet resistance or both are defined as voiding dysfunction. It needs high index of suspicion or else can go undiagnosed and can lead to magnitude of problems. The study aims to calculate the incidence of dysfunction of bladder in postnatal women and to study risk factors associated with development of bladder dysfunction and management strategies in cases of bladder dysfunction. Methods: Authors did a prospective observational study in a tertiary care hospital. 200 postpartum women were screened for complaints of voiding dysfunction within 6 hours of removal of catheter in post caesarean patients and of normal vaginal delivery. Authors found that the voiding dysfunction was relatively common with an incidence of 20.20%. Following risk factors were analyzed: parity, mode of delivery, pain at suture site, baby weight, para-urethral tear. Results: Postpartum voiding dysfunction was found to be relatively common with statistically significant association found for pain at suture site and para urethral tear. Intra partum events contributed to voiding dysfunction. 93% of patients who with voiding dysfunction could be managed conservatively, and only 7% had to undergo intervention in the form of re catheterization. Conclusions: The early identification and treatment can reduce the pain and discomfort. Majority of the cases resolves with conservative management and nursing staff plays a key role in early detection of the symptoms.